Surface domain engineering in lithium niobate - Stanicki, Badrudin Jakob; Younesi, Mohammadreza; Loechner, Franz Johannes Friedrich; Thakur, Hitesh; Chang, Wei-Kun; Geiss, Reinhard; Setzpfandt, Frank; Chen, Yen-Hung; Pertsch, Thomas (OSA Continuum, 2020)
In this work, we present a systematic experimental study of surface electric field poling for creating periodically poled lithium niobate. We want to control the homogeneity and the duty cycle of the periodic structures as well as domain shape and size in general. The created domain patterns are analyzed by selective etching with subsequent scanning electron microscopy. We investigate theoretically and experimentally how the shape of electrodes influences the poling results. Furthermore, the influence of the temporal waveform and magnitude of the applied poling voltage pulse is studied. Our results enable to identify optimal experimental parameters for high-quality surface poling.
CRIS-Team Scopus Importer:2023-04-20